2021
DOI: 10.1055/a-1576-4351
|View full text |Cite
|
Sign up to set email alerts
|

Anticipate, Target and Characterize: MS²-anticipated C-glycosylflavones from Erythrococca anomala

Abstract: We herein report on the first chemical assessment of Erythrococca anomala (Juss. ex Poir.) Prain (Euphorbiaceae), a genus that was – to the best of our knowledge – not studied yet from a phytochemical perspective. A molecular networking strategy was implemented to rapidly identify the known specialized metabolites from untargeted MS/MS analyses of E. anomala leaves ethanolic extract. This strategy allowed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Pilon et al (2019) showed that the O -glycosylated flavonoid compounds can be well characterized with molecular networking [ 42 ]. Kouamé et al (2021) used a molecular network approach to cluster C -glycosylated flavones and annotate them [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilon et al (2019) showed that the O -glycosylated flavonoid compounds can be well characterized with molecular networking [ 42 ]. Kouamé et al (2021) used a molecular network approach to cluster C -glycosylated flavones and annotate them [ 43 ].…”
Section: Discussionmentioning
confidence: 99%